A visualizable strategy to real-time monitor chiral block copolypeptide assembly by AIE fluorescent probes - Zenghao Li; Yanan Liu; Jing Sun (Supramolecular Materials)
Aggregation-induced emission (AIE) luminogens show great potential in many applications. In this study, we have synthesized diblock copolymers poly (ethylene glycol) -b-poly (9-anthrylmethyl-L-lysine) (PEG-b-PLLys-An) and poly (ethylene glycol) -b-poly (9-anthrylmethyl-D-lysine) PEG-b-PDLys-An with opposite handedness by ring-opening polymerization and post-modification. Both diblock copolymers can self-assemble into spherical micelles or planar connected disc-like aggregates at different water fractions. In addition, the copolymers present a typical AIE process concomitant with the self-assembly process. To facilitate the study of chain exchange kinetics, we develope a novel visualizable strategy based on fluorescence variation. This strategy allows us to monitor the real-time chain exchange process by mixing equimolar solutions of PEG44-b-PDLys20-An and PEG44-b-PLLys20-An with varying water volume fractions. We indicate that chain exchange predominantly occurs at low water fractions through a single-molecule extraction and redistribution mechanism rather than micellar fission and fusion. In contrast, the micelles appear to be ''kinetically frozen'' at high water fractions, suggesting suppressed chain exchange under these conditions. Importantly, our approach offers a visually observable method for probing the dynamics of micellar chain exchange in real time.